1975
DOI: 10.1111/j.1399-3054.1975.tb03851.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sapwood of Roots of Norway Spruce, Attacked by Fomes annosus

Abstract: Acetone extracts of sapwood and reaction zone of spruce roots attacked by Fomes annosus, collected in February, June and October, were separated into resinous and phenolic fractions. The fractions were further separated by column, thin layer and gas liquid chromatography, followed by biological tests, using Fomes annosus and other rot fungi. The reaction zone contained quantitatively less light petroleum soluble compounds than the sapwood but more acids. The phenolic content was about ten times higher in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…According to several authors, the light petroleum extractives range between 0.6-2.4 /o in the sapwood, 0.2-2.0% in the reaction zone, 0.04-2.5% in the H. tiwwoswm-decayed wood, and 0.8-2.3% in the heartwood on ad.wt basis (AGUINAGALDE and CERNY 1974;ALCUBILLA et al 1974;POPOFF et al 1975;EKMAN and VON WEISSENBERG 1979). Although obtained during the initial months of infection, our results agree approximately ith the values cited above.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to several authors, the light petroleum extractives range between 0.6-2.4 /o in the sapwood, 0.2-2.0% in the reaction zone, 0.04-2.5% in the H. tiwwoswm-decayed wood, and 0.8-2.3% in the heartwood on ad.wt basis (AGUINAGALDE and CERNY 1974;ALCUBILLA et al 1974;POPOFF et al 1975;EKMAN and VON WEISSENBERG 1979). Although obtained during the initial months of infection, our results agree approximately ith the values cited above.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies found that light petroleum extracts from the reaction zone inhibited H. annosum (POPOFF et al 1975;EKMAN 1980). In bioassays Norway spruce oleoresin also inhibited growth oi H. annosum (SHAIN 1971).…”
Section: Discussionmentioning
confidence: 96%
“…, have different specificities, and that the activities of HpLcc2 and P450s are linked, both possibly participating in the degradation of lignin in a sequential manner. Pioneer studies (Shain, 1971;Shain and Hillis, 1971;Johansson and Theander, 1974;Popoff et al, 1975) showed that the reaction zone forming in Norway spruce against Heterobasidion is enriched with phenolics, particularly lignans, and that many of these compounds have a fungistatic but not deleterious effect against the pathogen. Using a bioassay, Popoff et al (1975) showed that presumably a laccase from H. annosum is able to detoxify some of the lignans from the reaction zone.…”
Section: Identification Of Differentially Expressed Pathogen Genesmentioning
confidence: 99%
“…On the contrary, perennial plants and in particular conifers have been little studied in this respect. Concerning H. annositrn the only reports available discuss the infection process in bark and woody tissues of P. abies (Peek et al 1972;Popoff et al 1975;Johansson and Stenlid 1985;Stenlid and Johansson 1987;Lindberg and Johansson 1992) and Picea sitchensis (Woodward and Pearce 1988). However, for more detailed studies of physiological and structural responses to infection, such material is too complex and variable and also subject to stress influence.…”
Section: Introductionmentioning
confidence: 95%